Sinergi Usaha Lokal Menuju Kinerja Global: Program Pemberdayaan Ekonomi Kreatif Berbasis Kolaborasi Di Kuningan, Semarang - Diah Nurul Bayu P; Pipit Sundari; Bayu Sapta Adi N; Heni Subekti; Aulia Arma (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to empower micro, small and medium enterprises (MSMEs) in the creative economy sector in the Kuningan area, Semarang, by strengthening the capacity of work teams based on collaboration and synergy of local potential. The main problems faced by MSMEs in this area are weak teamwork, limited innovation and the suboptimal use of digital networks and cross-community promotion. This program is designed with a participatory and collaborative approach, involving intensive training, mentoring and creative forums across actors. The results of the activity show that MSMEs who participate in the program experience significant improvements in terms of collaborative capabilities, product innovation, and expansion of market networks. This article is expected to be a reference in developing a model for empowering MSMEs based on local wisdom and teamwork in urban-rural areas such as Kuningan, Semarang.